Microring resonator for transmission of solitons via wired/wireless optical communication - Amiri, I. S. (Optical Society of India, 2016)
A system of soliton array (SA) for optical communication using the wired/wireless link is presented. Gaussian laser beam with relevant parameters is input into the rings system. Here, bright soliton with Full Width at Half Maximum (FWHM) and Free Specrum Range (FSR) of 120 ps and 370 ps are generated respectively. We demonstrate that SA can be obtained by a series of micro ring resonators with input optical laser pulse. A PIN photodetector with responsivity of 1 A/W and dark current of 10 nA is used to convert the optical pulses to array of radio frequency (RF). Here, transmission of SA via 70 km fiber optics and 25 m wireless has been investigated.